The Effect Of Dividend Policy, Profitability And Liquidity On Firm Value: Evidence From Manufacturing Companies Listed On The Indonesia Stock Exchange - Dian Fajar Ayu; Romansyah Sahabuddin; Nurman (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
: Research approach was employed using panel data regression analysis. Model selection was determined through a series of diagnostic tests, namely the Redundant Fixed Effects Test and the Hausman Test, which indicated that the Fixed Effects Model (FEM) is the most appropriate estimation method. The data used are secondary data obtained from the companies’ annual financial reports during the research period. The results show that, individually, liquidity has a statistically significant positive effect on firm value, whereas dividend policy and profitability do not exhibit significant effects. This suggests that a company’s ability to meet its short-term obligations serves as a positive signal to investors, enhancing their perception of the firm’s stability and trustworthiness in terms of performance. Meanwhile, the insignificance of dividend policy and profitability implies that investors do not rely solely on these factors when evaluating firm value instead, they may consider broader strategic, market, or macroeconomic indicators. The coefficient of determination (R²) is 0.848588, indicating that approximately 84.85% of the variation in firm value can be explained by the combined influence of dividend policy, profitability, and liquidity, while the remaining 15.15% is attributed to other factors outside the scope of this study.